School Director and Change Management. - Wangthanomsak , Mattana; Suksodkiew, Vorakarn; Tiachareon, Saisuda; Intraprasert , Pornpun (Saengtham College Journal, 2021)
VUCA world, a complicated and fast changing world, has significant impacts on every organization, including the school. Only the organization with the ability to recognize the need for change and adapt to the change, can develop and survive. Hence, change management is the organizational-wide process to reduce potential negative fallout of the changes, to support the development and adaptability of the personnel, and to prepare the personnel for changes. Organization leader plays an important role in guiding the organization to go through changes effectively. This article briefly explains what change is, and how school leader copes with changes. A School Leader plays a role of a situation assessor, a change initiator, a communicator, a facilitator, a motivator, and a curator.